Motivic homotopy theory lectures - Dundas B I; Summer School on Motivic Homotopy Theory; Summer school on motivic homotopy theory Nordfjordeid, Norway 02-Aug (Berlin Springer-Verlag, 2007)
This book is based on lectures given at a summer school on motivic homotopy theory at the Sophus Lie Centre in Nordfjordeid, Norway, in August 2002. Aimed at graduate students in algebraic topology and algebraic geometry, it contains background material from both of these fields, as well as the foundations of motivic homotopy theory.
Keywords: Algebraic geometry; Algebraic topology; Homological algebra; K-theory